Pendekatan Fraud Heptagon Model dalam Mendeteksi Manipulasi Laba: Studi Empiris Perusahaan BUMN Non-Keuangan - Marisa Angelica Nur Faisal; Fefri Indra Arza (Universitas Negeri Padang, 2026)
This study examines the influence of pressure, opportunity, rationalization, capability, arrogance, ignorance, and greed on profit manipulation. The research utilizes quantitative techniques to examine the theory and assess the connection among these variables. The study population comprises non-financial, state-owned enterprises (SOEs) that were traded on the Indonesia Stock Exchange (IDX) between 2019 and 2023. The research utilized purposive sampling with 80 observations. Logistic regression was employed for the analysis. The findings suggest that pressure and rationalization negatively impact profit manipulation, while ignorance positively impact it. Meanwhile, opportunity, capability, arrogance, and greed do not impact profit manipulation.